2021
DOI: 10.1002/onco.13858
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy in Glioblastoma Management: From Current Research to Future Perspectives

Abstract: Glioblastoma (GBM) is the most common primary tumor of the central nervous system. Arising from neuroepithelial glial cells, GBM is characterized by invasive behavior, extensive angiogenesis and genetic heterogeneity that contributes to poor prognosis and treatment failure.Currently, there are several molecular biomarkers available to aid in diagnosis, prognosis and predicting outcome of the treatment; however, all require the biopsy of tumor tissue.Nevertheless, a tissue sample from a single location has its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 144 publications
(210 reference statements)
0
46
0
Order By: Relevance
“…In the future, determination of changes in the molecular signature of gliomas and very early detection of therapy response or failure will gain further importance. Whether several techniques and concepts of “liquid biopsy” using CSF, plasma, or even urine may complement or even replace stereotactic biopsies for at least some indications remains yet uncertain ( 61 66 ). Also, molecular imaging using novel specific tracers might help to non-invasively better characterize gliomas in the future ( 67 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the future, determination of changes in the molecular signature of gliomas and very early detection of therapy response or failure will gain further importance. Whether several techniques and concepts of “liquid biopsy” using CSF, plasma, or even urine may complement or even replace stereotactic biopsies for at least some indications remains yet uncertain ( 61 66 ). Also, molecular imaging using novel specific tracers might help to non-invasively better characterize gliomas in the future ( 67 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research showed that circulating free DNA, circulating tumor cell, circulating tumor DNA and microRNA in blood or cerebrospinal fluid were used for GBM early diagnosis, early tumor progression detection, monitoring of tumor treatment response, personalized treatment identification, such as EGFR, TGF-b, IDH, miR-21and so on. Those gene play vital role in GBM early diagnosis and specific therapy and could be detected in liquid biopsy for overcoming the solid cancer biopsy limits (14).Recently, an increasing number of studies have demonstrated that miRNA-mediated ceRNA crosstalk plays a vital role in cancers, including glioma (9,15). As TCGA glioma data lack normal brain control data, comprehensive analyses of the DEmRNA and noncoding RNA profiles in glioma, based on large-scale RNA sequencing platforms, are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of valuable biomarkers hinders the clinical management of glioma patients. Liquid biopsies may represent a reliable and non-invasive technique [ 29 ].…”
Section: Discussionmentioning
confidence: 99%